A brief review on the validation of biology methods for COVID-19 detection - Chung, Le Thi Kim; Vung, Nguyen Dang; Uyen, Ngo Thi; Hanh, Bui Thi Minh; Huong, Le Thi; Hien, Pham Thi; Xuan, Le Thi Thanh; Ha, Nguyen Thuy; Dat, Dao Xuan (Frontiers in Tropical Diseases, 2022)
The COVID-19 global pandemic has been going on for more than two years, and the evolution of SARS-CoV-2 with many variants of concern still poses a risk to public health. Sufficient access to qualified and validated testing plays an important role in detecting and alerting trends of the pandemic and provides evidence for making decisions in preventive strategies and policies. Depending on the method of testing and laboratory conditions, validation parameters (i.e., analytical sensitivity, limit of detection, diagnostic sensitivity, analytical specificity, diagnostic specificity, repeatability, reproducibility, robustness, positive predictive value, negative predictive value, applicability, practicability, and time to results) can be very different. With three main types of COVID-19 detection kits available, comprising nucleic acid, serological, and antigen detection, the kind of validation parameters that should be used becomes a complicated consideration and takes time to assess. Our review provides valuable and comprehensive information for laboratories in the assessment and selection of the optimal parameters to validate new COVID-19 test kits.